Reduced Population of CD36-/ABCA1+ Macrophages is Correlated with An Increase of Coronary Artery Disease Risk Markers in Type 2 Diabetes Mellitus - Nur Irawati; Heri Wibowo; Ani Retno Prijanti; Rona Kartika; Dicky Levenus Tahapary (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Cluster of differentiation (CD)36 and adenosine triphosphate-binding cassette transporter A1 (ABCA1) are 2 macrophages-expressed receptors that promote cholesterol uptake and efflux, in which their imbalance might be associated with the foam cell formation risk. Type 2 diabetes mellitus (T2DM) has been correlated with the increase of this plaque formation. Therefore, it is necessary to determine whether expression of CD36 and ABCA1 in macrophages are correlated with coronary artery disease (CAD) risk markers in T2DM cases.METHODS: Peripheral blood mononuclear cells (PBMC) were isolated from 13 diabetic patients and 11 healthy donors. Then, the PBMC-derived macrophages were cultured with supplement of oxidized low-density lipoprotein (ox-LDL) or lipopolysaccharide (LPS). Expression of CD36 and ABCA1 was measured using flowcytometry, meanwhile the supernatant concentration of interleukin (IL)-1b and IL-10 was measured by multiplex immunoassay.RESULTS: T2DM subjects more likely to have low proportion of CD36-ABCA+ macrophages compared to healthy donors (p=0.041) and it had negative correlation with glucose homeostasis and insulin resistance markers, including fasting blood glucose (FBG, r=-0.408, p=0.048), glycated hemoglobin (HbA1c, r=-0.380, p=0.049), triglyceride glucose index (r=-0,518, p=0.009), and high-sensitivity C-reactive protein (hs-CRP, r=-0.556, p=0.005). Moreover, it also had a negative correlation with atherogenic markers such as triglyceride (r=-0.417, p=0.043), triglyceride/HDL, and LDL/HDL, but had positive correlation with HDL (r=0.540, p=0.007). Most of T2DM subjects had high IL-1β/IL-10 ratio after ox-LDL and LPS stimulation (p=0.02 and p=0.05, respectively).CONCLUSION: Reduced proportion of CD36-ABCA1+ macrophages followed with high IL-1β/IL-10 can be a marker of CAD in T2DM.KEYWORDS: type 2 diabetes mellitus, coronary artery disease, macrophages, ABCA1, CD36